Faktor-Faktor Penyebab Anak Menjadi Korban Kekerasan Dalam Rumah Tangga Dan Tanggung Jawab Negara - Imelda Aprilia Putri; Asep Suherman (CV. ITTC INDONESIA, 2024)
This article examines the factors causing children to become victims of domestic violence (DV) and the state's responsibility in protecting children's rights. The legal issue raised is the lack of legal protection for child victims of domestic violence and how law enforcement and state policies are not yet optimal in preventing and addressing these cases. The aim of this study is to identify the factors contributing to violence against children within households and evaluate the role of the state in prevention and child protection efforts. The methodology used is literature review with a normative juridical approach by analyzing relevant laws and case studies from official reports. The results show that economic factors, low parental education, and patriarchal culture are the main causes, while the state's efforts remain insufficient to comprehensively tackle this issue.